Photo-crosslinking conductive ink based on aliphatic polycarbonate as well as preparation method and application of photo-crosslinking conductive ink
By using the carbonate monomer copolymerization reaction initiated by PEG2000 in conductive ink to synthesize aliphatic polycarbonate polymers, combined with ultraviolet cross-linking technology, the problems of unstable conductivity, high cost and nanoparticle agglomeration in the processing process of conductive ink are solved, and the rapid curing and excellent mechanical properties of ink are achieved, and the scope of application is broadened.
Patent Information
- Application Number
- CN202411790139.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-06
- Publication Date
- 2025-02-28
AI Technical Summary
The existing conductive inks have problems such as unstable conductivity, high cost, easy oxidation and nanoparticle agglomeration during processing in applications, which limits its promotion in large-scale and low-cost applications.
The carbonate monomer 5-methyl-5-carboxytrimethylene carbonate copolymerization reaction initiated by PEG2000 was synthesized to form an aliphatic polycarbonate polymer, and mixed with choline chloride, acrylic acid, zinc chloride and photocrosslinking agent to achieve rapid curing of ink and high-intensity three-dimensional structure formation through ultraviolet crosslinking technology.
It realizes rapid curing of conductive ink, excellent mechanical properties and biocompatibility, reduces production costs, and broadens its application scope in medical devices, biosensors and other fields.
Smart Images

Figure CN119529193A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of conductive inks, and in particular to a photo-crosslinked conductive ink based on aliphatic polycarbonate, and a preparation method and application thereof. Background Art
[0002] Conductive ink, as the core material in printed electronics technology, has attracted widespread attention in academia and industry in recent years. As electronic devices develop towards lightweight, flexible, low-cost and environmentally friendly, traditional manufacturing processes face many challenges. The emergence of conductive ink provides a new solution for the manufacture of electronic devices. Using printing technology, conductive patterns can be directly prepared on various substrates to achieve low-temperature, low-cost, large-area and flexible production of electronic devices. This technology has revolutionized the way electronic devices are manufactured and brought unlimited possibilities for the design and production of future electronic products.
[0003] At present, the common conductive inks on the market are mainly based on metal nanoparticles, such as silver and copper, and carbon materials, such as graphene and carbon nanotubes. Although these materials have excellent conductive properties, they also have some problems in practical applications. Taking silver nanoparticles as an example, although they have excellent conductivity, they are expensive, which limits their promotion in large-scale, low-cost applications. Although copper nanoparticles are low in cost, they are easily oxidized, resulting in decreased conductivity and affecting the stability and service life of the device. In addition, metal nanoparticles are prone to agglomeration during processing, affecting the stability and printing performance of the ink. Carbon-based materials such as graphene and carbon nanotubes have excellent mechanical properties and conductivity, but their dispersibility in ink is poor, and they are easy to form agglomerations, resulting in decreased stability and conductive properties of the ink. Moreover, the large-scale production and quality control of graphene also face huge challenges, which limit its widespread promotion in practical applications. Summary of the invention
[0004] This application is made in view of the above-mentioned problems, and its purpose is to provide a photo-crosslinked conductive ink based on aliphatic polycarbonate, and its preparation method and application, which is a mixture of aliphatic polycarbonate polymer synthesized by copolymerization of carbonate monomer 5-methyl-5-carboxytrimethylene carbonate initiated by PEG2000, choline chloride, acrylic acid, zinc chloride and a photo-crosslinking agent. The ink can be quickly cross-linked under ultraviolet light to form a high-strength three-dimensional structure, has excellent mechanical properties and biocompatibility, and is suitable for medical devices, personalized customized products and other fields.
[0005] A first aspect of the present application provides a photo-crosslinked conductive ink based on aliphatic polycarbonate, comprising an aliphatic polycarbonate polymer, a plasticizer, a crosslinking agent, a crosslinking catalyst and a photo-crosslinking agent.
[0006] In any embodiment, the composition comprises the following parts by weight: 5-15 parts by weight of aliphatic polycarbonate polymer, 0.5-1.5 parts by weight of plasticizer, 0.5-1.5 parts by weight of crosslinking agent, 0.2-0.8 parts by weight of crosslinking catalyst and 0.1-0.3 parts by weight of photocrosslinking agent.
[0007] In any embodiment, the plasticizer is choline chloride, the cross-linking agent is acrylic acid, the cross-linking catalyst is zinc chloride, and the photocross-linking agent is benzophenone.
[0008] In any embodiment, it is composed of the following parts by weight: 10 parts by weight of aliphatic polycarbonate polymer, 1 part by weight of plasticizer (choline chloride), 1 part by weight of crosslinking agent (acrylic acid), 0.5 part by weight of crosslinking catalyst (zinc chloride) and 0.2 part by weight of photocrosslinking agent (benzophenone).
[0009] In any embodiment, the viscosity of the ink is 200-300 mPa·s.
[0010] A second aspect of the present application also provides a method for preparing a photo-crosslinked conductive ink, comprising the following steps:
[0011] (1) Synthetic aliphatic polycarbonate polymers;
[0012] (2) Preparing conductive ink: adding aliphatic polycarbonate polymer, plasticizer, crosslinker, crosslinking catalyst and photocrosslinker in a certain proportion into a mixing container and stirring at 100-300 revolutions per minute (rpm) for 5-15 minutes to ensure that the components are fully mixed; then, ultrasonically treating the mixture for 5-10 minutes using an ultrasonic processor.
[0013] In any embodiment, the synthesis of the aliphatic polycarbonate polymer is as follows: first, polyethylene glycol and 5-methyl-5-carboxytrimethylene carbonate are added to a polymerization tube in a certain proportion under nitrogen protection, and a proper amount of polymerization catalyst is added and the tube is sealed with a vacuum flame; then the reaction system is heated to 120-160° C. under anhydrous and oxygen-free conditions, and the reaction is maintained for 18-28 hours. After the reaction is completed, it is quickly cooled to room temperature; then, the aliphatic polycarbonate polymer is obtained by centrifugal separation; finally, the separated polymer is dried in a vacuum drying oven for 24 hours.
[0014] In any embodiment, the PEG2000 and 5-methyl-5-carboxytrimethylene carbonate are mixed in a molar ratio of 1:1.
[0015] In any embodiment, the amount of the polymer catalyst added is 0.3-0.6% of the total mass of the reactants.
[0016] In any embodiment, after cooling to room temperature, icy methanol is added to precipitate the polymer, and small molecules are removed by sedimentation.
[0017] In any embodiment, the amount of glacial methanol added is 2-3 times the amount of the reactants.
[0018] In any embodiment, the molecular weight of the polyethylene glycol is 1800-2200.
[0019] In any embodiment, the mass ratio of the polyethylene glycol to MCC is 0.1 to 1.5, and the mass ratio of the polymerization catalyst to MCC is 0.01 to 0.03.
[0020] In any embodiment, the polymerization catalyst is stannous octoate.
[0021] In any embodiment, the reaction temperature is 130 to 160 ℃ The reaction time is 15-36h.
[0022] In any embodiment, the aliphatic polycarbonate polymer is 5-15 parts by weight, the plasticizer is 0.5-1.5 parts by weight of choline chloride, the crosslinking agent is 0.5-1.5 parts by weight of acrylic acid, the crosslinking catalyst is 0.2-0.8 parts by weight of zinc chloride and the photocrosslinking agent is 0.1-0.3 parts by weight of benzophenone.
[0023] In any embodiment, the purity of the 5-methyl-5-carboxytrimethylene carbonate monomer is greater than 99%.
[0024] A third aspect of the present application provides an application of conductive ink in 3D printing.
[0025] Beneficial effects of this application:
[0026] 1) The present invention uses 5-methyl-5-carboxytrimethylene carbonate, a carbonate monomer initiated by PEG2000, to synthesize aliphatic polycarbonate polymers through copolymerization as the main matrix material of conductive ink; it has high biocompatibility: aliphatic polycarbonate is a biodegradable polymer material with excellent biocompatibility, suitable for various medical and bioengineering fields; environmental friendliness: the material can be degraded by microorganisms in the natural environment, reducing environmental pollution and meeting the requirements of sustainable development; good mechanical properties: the polymer material has both high strength and flexibility, and is suitable for devices that require excellent mechanical properties. Therefore, by using this innovative material system, the conductive ink not only has good conductive properties, but also has biocompatibility and environmental protection, broadening its application range in medical devices, biosensors and other fields.
[0027] 2) The present invention adds a photocrosslinking agent to the conductive ink, so that it can be quickly crosslinked under ultraviolet light irradiation, achieve efficient curing, and form a high-strength three-dimensional structure. The crosslinking reaction can be triggered in a short time by ultraviolet light irradiation, which significantly shortens the curing time and improves production efficiency. And by adjusting the intensity and irradiation time of the ultraviolet light, the degree of crosslinking can be accurately controlled to meet the needs of different applications. Compared with thermal curing and other methods, the ultraviolet light curing process has lower energy consumption and is more energy-saving and environmentally friendly. In general, the application of rapid ultraviolet light crosslinking technology simplifies the curing process of the conductive ink, improves production efficiency, and reduces costs; at the same time, the temperature during the curing process is low, which avoids the influence of high temperature on the material properties, which is conducive to the preparation of high-quality conductive structures.
[0028] 3) Under ultraviolet light, the conductive ink can quickly form a high-strength three-dimensional cross-linked structure, giving the material excellent mechanical properties. The cross-linked polymer network structure improves the mechanical strength of the material, can withstand large tensile and bending stresses, and has high strength and good toughness; the three-dimensional cross-linked structure makes the material more stable and durable in physical and chemical environments; the mechanical properties of the material can be adjusted by adjusting the cross-linking density and formula ratio to meet different application requirements. The excellent mechanical properties ensure that the conductive ink can maintain structural integrity and functional stability in practical applications, and is especially suitable for flexible electronic devices and wearable devices that require frequent bending and stretching.
[0029] 4) The conductive ink of the present invention has good conductivity and biocompatibility, which expands its application areas: Medical devices: It can be used to manufacture implantable electronic devices, biosensors, smart bandages, etc., which are safe in contact with human tissue and meet the requirements of medical-grade devices; and it is suitable for 3D printing and flexible electronic manufacturing, and can customize electronic products according to individual needs, such as smart clothing, wearable devices, etc.; Internet of Things and smart manufacturing: It can be used to print electronic tags and flexible circuits to achieve low-cost, large-scale production of electronic devices; The versatility of conductive ink makes it have great application value in the fields of medical care, consumer electronics, Internet of Things, etc., meets the needs of modern electronic devices for high-performance, multifunctional materials, promotes the development of related industries and technological innovation, and has a wide range of applications.
[0030] 5) The preparation process is simple and can be mass-produced
[0031] The conductive ink of the present invention has simple preparation steps, controllable process, and is easy to realize industrial production. The synthesis of aliphatic polycarbonate polymer is carried out under nitrogen protection, the reaction conditions are mild, and the operability is strong; the preparation of conductive ink ensures the uniform mixing and stability of each component through low-speed stirring and ultrasonic treatment; the raw materials used are easy to obtain, the energy consumption in the process is low, and it has cost advantages. The simple preparation process reduces the production cost and is convenient for large-scale promotion and application; at the same time, the controllability of the process ensures the stability and consistency of product quality, meeting the requirements of industrial production for process and quality. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 1HNMR spectrum of the polymer prepared in Example 1 of the present invention;
[0033] Figure 2 This is the DSC spectrum of the polymer prepared in Example 2 of the present invention;
[0034] Figure 3 This is the TGA spectrum of the polymer prepared in Example 2 of the present invention;
[0035] Figure 4 This is the stretching spectrum of the polymer prepared in Example 2 of the present invention. DETAILED DESCRIPTION
[0036] Hereinafter, the photo-cross-linked conductive ink based on aliphatic polycarbonate and its preparation method and application embodiments of the present application are specifically disclosed with appropriate reference to the accompanying drawings. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structures are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the drawings and the following descriptions are provided for those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0037] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0038] If not otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0039] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0040] If there is no special explanation, all steps of the present application can be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (a) and (b), which means that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, the method may further include step (c), which means that step (c) may be added to the method in any order. For example, the method may include steps (a), (b) and (c), or may include steps (a), (c) and (b), or may include steps (c), (a) and (b), etc.
[0041] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0042] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0043] In order to overcome the problems of existing conductive inks, researchers explored conductive inks based on polymer materials. Polymer-based conductive inks have excellent processability, flexibility and controllability. In particular, the combination of photocrosslinking technology provides new ideas for the research and development of conductive inks. Photocrosslinking is a method that uses photoinitiators to generate free radicals or ions under the irradiation of light of a specific wavelength, thereby initiating a crosslinking reaction between polymer chains; compared with traditional thermal curing methods, photocrosslinking has the advantages of fast curing speed, low energy consumption, and environmental friendliness. Through photocrosslinking, the ink can be quickly cured in a short time to form a conductive film with excellent mechanical properties and surface quality, which is of great significance for meeting the needs of modern electronic devices for high-performance, low-cost and environmentally friendly materials.
[0044] In terms of the selection of polymer matrix materials, aliphatic polycarbonate polymers are used due to their unique properties. Aliphatic polycarbonates have good biocompatibility and degradability, excellent mechanical properties, and are easy to be functionally modified by chemical means. By regulating its molecular weight and structure, polymer materials with different properties can be obtained to meet the needs of different applications. When synthesizing aliphatic polycarbonate polymers, polyethylene glycol (PEG) is often used as an initiator to undergo a ring-opening copolymerization reaction with carbonate monomers. PEG has good hydrophilicity and can give the polymer appropriate hydrophilicity, which helps to evenly disperse the conductive filler in the ink. In addition, the molecular weight of PEG is adjustable, and by selecting PEG of different molecular weights, the molecular weight and segment flexibility of the polymer can be regulated, thereby affecting the performance of the final material.
[0045] In order to further improve the conductivity and processing performance of the ink, ionic liquids and functional monomers are introduced into the system. Choline chloride, as an environmentally friendly ionic liquid, is derived from biomass, is biodegradable, has good conductivity and ion mobility, and can improve the overall conductivity of the ink; it also has strong solubility and can dissolve a variety of organic and inorganic substances, which helps to form a uniform ink system. Acrylic acid, as a functional monomer containing double bonds, can undergo free radical polymerization under the action of photoinitiators to form a three-dimensional cross-linked network, thereby improving the mechanical strength and stability of the ink after curing; the acrylic acid group can also enhance the bonding force between the conductive film and the substrate surface and improve adhesion. Zinc chloride may act as a cross-linking catalyst in this system, promoting the polymerization reaction of acrylic acid, increasing the cross-linking rate and cross-linking density; in addition, the zinc ions in zinc chloride also help to improve the ionic conductivity of the material.
[0046] UV curing technology has been widely used in the fields of coatings, inks and adhesives, and its advantages in conductive inks are particularly prominent. UV curing can complete the curing process in a short time, greatly improving production efficiency and being suitable for continuous production. Since no heating is required, damage to heat-sensitive substrates (such as plastics, paper, textiles, etc.) caused by high temperatures can be avoided, thus expanding the scope of application. UV curing technology is also environmentally friendly and energy-saving, solvent-free, and low in energy consumption, meeting the requirements of green manufacturing. These advantages make UV curing technology have important application potential in the development of new conductive inks.
[0047] In the application of conductive ink, in addition to conductive properties, mechanical properties and surface quality are also crucial factors. Electronic devices may be subjected to various mechanical stresses during use, such as bending, stretching and compression. Excellent mechanical properties can ensure the integrity of the conductive path and avoid cracking and failure. In addition, a flat and smooth surface helps to improve the performance of electronic devices, reduce resistance and energy loss, and also improve the aesthetics of the product. Through photocrosslinking technology, a dense crosslinking network can be formed, which significantly improves the mechanical properties and surface quality of the conductive film. This is especially important for the manufacture of flexible electronic devices, because these devices need to maintain stable performance under repeated bending and deformation.
[0048] The present application develops a novel photo-crosslinked conductive ink based on aliphatic polycarbonate polymers. By mixing aliphatic polycarbonate polymers with choline chloride, acrylic acid, zinc chloride and a photoinitiator, and using ultraviolet light for crosslinking treatment, a conductive ink with excellent performance can be prepared. The ink not only overcomes the shortcomings of traditional conductive inks, achieves rapid curing and performance improvement, but also has the characteristics of being green and environmentally friendly. The preparation method of this conductive ink is simple, the raw materials are easily available, and it has good industrial prospects.
[0049] This new conductive ink has broad application prospects in the manufacture of flexible electronic devices. It can be used to manufacture flexible displays, wearable devices, electronic skin and other devices that have high requirements for mechanical properties and flexibility. Due to the biocompatibility and degradability of the material, it can also be used in the biomedical field to manufacture biosensors, implantable devices, etc. In addition, the ink can also be used to print electronic tags and sensors to realize the Internet of Things and smart logistics. In the field of energy devices, this conductive ink can be used to prepare flexible solar cells, supercapacitors and other energy storage and conversion devices. These applications have put forward higher requirements on the performance of conductive inks, and the new photo-crosslinked conductive ink just meets these needs.
[0050] In summary, the novel photo-crosslinked conductive ink based on aliphatic polycarbonate polymer developed by the present invention can meet the requirements of modern electronic devices for high performance, low cost and environmentally friendly materials, and is an important topic in the fields of materials science and electronic technology. The emergence of this conductive ink not only enriches the types of conductive inks, but also provides new material options for the manufacture of flexible electronic devices. At the same time, the use of ultraviolet light crosslinking technology realizes the rapid curing of the conductive ink, improves production efficiency, and helps to achieve large-scale production.
[0051] In summary, the development of new photo-crosslinked conductive ink based on aliphatic polycarbonate polymer not only has important academic value, but also has broad application prospects. It provides new ideas for the research and application of conductive ink and brings new breakthroughs to the development of electronic technology.
[0052] A photo-crosslinked conductive ink based on aliphatic polycarbonate, which is a mixture of an aliphatic polycarbonate polymer synthesized by copolymerization of carbonate monomer 5-methyl-5-carboxytrimethylene carbonate initiated by PEG2000, choline chloride, acrylic acid, zinc chloride and a photo-crosslinking agent. The ink can be rapidly crosslinked under ultraviolet light to form a high-strength three-dimensional structure, has excellent mechanical properties and biocompatibility, and is suitable for medical devices, personalized customized products and other fields.
[0053] A photo-crosslinking conductive ink based on aliphatic polycarbonate comprises an aliphatic polycarbonate polymer, a plasticizer, a crosslinking agent, a crosslinking catalyst and a photo-crosslinking agent.
[0054] In any embodiment, the composition comprises the following parts by weight: 5-15 parts by weight of aliphatic polycarbonate polymer, 0.5-1.5 parts by weight of plasticizer, 0.5-1.5 parts by weight of crosslinking agent, 0.2-0.8 parts by weight of crosslinking catalyst and 0.1-0.3 parts by weight of photocrosslinking agent.
[0055] Preferably, a photo-crosslinking conductive ink is composed of 5-15 parts by weight of an aliphatic polycarbonate polymer, 0.5-1.5 parts by weight of a plasticizer, 0.5-1.5 parts by weight of a crosslinking agent, 0.2-0.8 parts by weight of a crosslinking catalyst and 0.1-0.3 parts by weight of a photo-crosslinking agent.
[0056] Preferably, it is composed of the following parts by weight: 10 parts by weight of aliphatic polycarbonate polymer, 1 part by weight of plasticizer, 1 part by weight of crosslinking agent, 0.5 part by weight of crosslinking catalyst and 0.2 part by weight of photocrosslinking agent.
[0057] The selection and dosage of these ingredients are carefully designed to ensure that the ink has excellent mechanical properties and biocompatibility, suitable for medical devices and personalized customized products. The addition of plasticizers helps to improve the fluidity and flexibility of the ink, while crosslinkers and photocrosslinkers ensure that the ink can be quickly cured under light, improving production efficiency. To ensure the performance of the final product, the concentration and purity of all ingredients must be strictly controlled to avoid the influence of impurities on the polymerization reaction, thereby ensuring the quality and stability of the conductive ink.
[0058] In any embodiment, the plasticizer is choline chloride, the cross-linking agent is acrylic acid, the cross-linking catalyst is zinc chloride, and the photocross-linking agent is benzophenone.
[0059] In any embodiment, the viscosity of the ink is 200-300 mPa·s.
[0060] A second aspect of the present application also provides a method for preparing a photo-crosslinked conductive ink, comprising the following steps:
[0061] (1) Synthetic aliphatic polycarbonate polymers;
[0062] (2) Preparing conductive ink: adding aliphatic polycarbonate polymer, plasticizer, crosslinker, crosslinking catalyst and photocrosslinker in a certain proportion into a mixing container and stirring at 100-300 revolutions per minute (rpm) for 5-15 minutes to ensure that the components are fully mixed; then, ultrasonically treating the mixture for 5-10 minutes using an ultrasonic processor.
[0063] In any embodiment, the synthesis of the aliphatic polycarbonate polymer is as follows: first, polyethylene glycol and 5-methyl-5-carboxytrimethylene carbonate are added to a polymerization tube in a certain proportion under nitrogen protection, and a proper amount of polymerization catalyst is added and the tube is sealed with a vacuum flame; then the reaction system is heated to 120-160° C. under anhydrous and oxygen-free conditions, and the reaction is maintained for 18-28 hours. After the reaction is completed, it is quickly cooled to room temperature; then, the aliphatic polycarbonate polymer is obtained by centrifugal separation; finally, the separated polymer is dried in a vacuum drying oven for 24 hours.
[0064] In any embodiment, the PEG2000 and 5-methyl-5-carboxytrimethylene carbonate are mixed in a molar ratio of 1:1.
[0065] In any embodiment, the amount of the polymer catalyst added is 0.3-0.6% of the total mass of the reactants.
[0066] In any embodiment, after cooling to room temperature, icy methanol is added to precipitate the polymer, and small molecules are removed by sedimentation.
[0067] In any embodiment, the amount of glacial methanol added is 2-3 times the amount of the reactants.
[0068] In any embodiment, the molecular weight of the polyethylene glycol is 1800-2200.
[0069] In any embodiment, the mass ratio of the polyethylene glycol to MCC is 0.1 to 1.5, and the mass ratio of the polymerization catalyst to MCC is 0.01 to 0.03.
[0070] In any embodiment, the polymerization catalyst is stannous octoate.
[0071] In any embodiment, the reaction temperature is 130 to 160 ℃ The reaction time is 15-36h.
[0072] In any embodiment, the aliphatic polycarbonate polymer is 5-15 parts by weight, the plasticizer is 0.5-1.5 parts by weight of choline chloride, the crosslinking agent is 0.5-1.5 parts by weight of acrylic acid, the crosslinking catalyst is 0.2-0.8 parts by weight of zinc chloride and the photocrosslinking agent is 0.1-0.3 parts by weight of benzophenone.
[0073] In any embodiment, the purity of the 5-methyl-5-carboxytrimethylene carbonate monomer is greater than 99%.
[0074] A third aspect of the present application provides an application of conductive ink in 3D printing.
[0075] The specific preparation steps of the conductive ink of the present invention include:
[0076] (1) Synthesis of aliphatic polycarbonate polymer: First, prepare the materials required for synthesis, including PEG2000, 5-methyl-5-carboxytrimethylene carbonate, polymerization catalyst and solvent. Under nitrogen protection, PEG2000 and 5-methyl-5-carboxytrimethylene carbonate were added to the polymerization tube at a certain molar ratio, and the tube was sealed with a vacuum flame after adding an appropriate amount of catalyst. Then, the reaction system was heated to 140°C in anhydrous and oxygen-free conditions. ℃After the reaction is completed, the mixture is cooled to room temperature, and ice methanol is added to precipitate the polymer, which is then separated by centrifugation to obtain an aliphatic polycarbonate polymer. Finally, the separated polymer is dried in a vacuum drying oven for 24 hours.
[0077] If PEG2000 is selected as the initiator, its molecular weight is 2000, and it has good biocompatibility and chemical stability. The selection of PEG2000 is based on its ability to effectively initiate the polymerization process in the polymerization reaction, and its molecular structure can provide an appropriate chain growth rate. The main monomer is 5-methyl-5-carboxytrimethylene carbonate, and its purity is ensured to be higher than 99% to ensure the smooth progress of the polymerization reaction. The high purity of this monomer is crucial to the performance of the final polymer, because impurities may affect the efficiency of the polymerization reaction and the properties of the polymer. In addition, stannous octoate is used as a polymerization catalyst to promote the polymerization reaction. Stannous octoate can effectively accelerate the polymerization reaction and increase the reaction rate. During the entire polymerization process, it must be carried out under anhydrous and oxygen-free conditions to avoid the interference of moisture and oxygen on the polymerization reaction and ensure the quality and performance of the polymer. Among the prepared materials, all chemical reagents must undergo strict quality control to ensure that they meet the experimental requirements; the molecular weight and purity of polyethylene glycol must be tested by high-performance liquid chromatography (HPLC) to confirm that it meets the experimental standards; the purity of 5-methyl-5-carboxytrimethylene carbonate must also be analyzed by gas chromatography (GC) to ensure that it does not contain any impurities; the quality of stannous octoate must be confirmed by infrared spectroscopy (FTIR) to ensure the integrity of its chemical structure.
[0078] In the reaction step, PEG2000 and 5-methyl-5-carboxytrimethylene carbonate are first added to the polymerization tube in a certain molar ratio under nitrogen protection. The purpose of nitrogen protection is to remove moisture and oxygen in the air and ensure that the reaction environment is anhydrous and oxygen-free. Subsequently, after adding an appropriate amount of catalyst stannous octoate, the tube is vacuum flame sealed to ensure the sealing of the reaction system. Next, the reaction system is heated to 140°C under anhydrous and oxygen-free conditions and kept reacting for 24 hours. At this temperature, the polymerization reaction can be effectively carried out to form an aliphatic polycarbonate polymer. After the reaction is completed, it is quickly cooled to room temperature and ice methanol is added to precipitate the polymer. The addition of ice methanol helps to separate the polymer from the reaction system, and the precipitation process can remove unreacted monomers and by-products. Subsequently, the aliphatic polycarbonate polymer is obtained by centrifugation to ensure the purity and quality of the polymer. Finally, the separated polymer is dried in a vacuum drying oven for 24 hours to remove residual solvents and moisture to ensure the stability of the polymer. NMR can provide information about the molecular structure of the polymer, including chain length and branching, while FTIR is used to detect functional groups in the polymer to confirm its chemical structure and composition. In addition, the molecular weight of the polymer is tested to ensure that it is within the expected range. Molecular weight is usually determined by methods such as gel permeation chromatography (GPC) to evaluate the molecular weight distribution and uniformity of the polymer. The molecular weight of the polymer has an important influence on its physical and chemical properties, so the reaction conditions must be strictly controlled during the synthesis process to obtain the desired molecular weight.
[0079] (2) Preparation of conductive ink
[0080] The synthesized aliphatic polycarbonate polymer, choline chloride, acrylic acid, zinc chloride and photocrosslinker benzophenone were weighed in proportion. Choline chloride, as a plasticizer, can improve the fluidity and printing performance of the ink; acrylic acid, as a crosslinker, can enhance the adhesion and strength of the ink; zinc chloride, as a catalyst, can promote the photocrosslinking reaction. The above materials were added to a mixing container and stirred at a low speed in a stirrer for 10 minutes to ensure that the components were fully mixed to form a uniform conductive ink. The mixture was ultrasonically treated with an ultrasonic processor for 5-10 minutes to remove bubbles and ensure the uniformity and stability of the ink. The presence of bubbles may affect the printing quality, so special attention should be paid during the ink preparation process. The viscosity of the ink was tested using a viscometer to ensure that it was between 200-300mPa·s, which was suitable for the nozzle requirements of the 3D printer. The viscosity of the ink directly affects the fluidity and nozzle efficiency during the printing process, so it needs to be strictly controlled. During the ink preparation process, the order of addition and mixing time of each component need to be optimized to ensure that the performance of the ink is optimal. The optimal mixing time and stirring speed were determined experimentally to obtain a uniform ink. In addition, the pH value of the ink needs to be monitored to ensure that it is within the appropriate range to improve the stability and printing performance of the conductive ink.
[0081] Example
[0082] Hereinafter, the embodiments of the present application will be described. The embodiments described below are exemplary and are only used to explain the present application, and should not be construed as limiting the present application. If no specific techniques or conditions are indicated in the embodiments, the techniques or conditions described in the literature in this area or the product specifications are used. If the manufacturer is not indicated in the reagents or instruments used, they are all conventional products that can be obtained commercially.
[0083] Embodiment 1:
[0084] A preparation method of a photo-crosslinked conductive ink based on aliphatic polycarbonate comprises the following steps:
[0085] 1. Synthesis of aliphatic polycarbonate polymer based on 5-methyl-5-carboxytrimethylene carbonate initiated by PEG2000
[0086] (1) Material preparation: PEG2000 was selected as the initiator, with a molecular weight of 2000 and a monomer of 5-methyl-5-carboxytrimethylene carbonate with a purity higher than 99%;
[0087] In the reaction step, first, under nitrogen protection, PEG2000 and 5-methyl-5-carboxytrimethylene carbonate are added to the polymerization tube in a molar ratio of 1:1 (for example, 0.1 mole of 5-methyl-5-carboxytrimethylene carbonate is combined with 0.1 mole of PEG2000). Subsequently, an appropriate amount of catalyst stannous octoate is added, the amount of which is 0.5% of the total mass of the reactants (for 10 grams of reactants, 0.05 grams of stannous octoate can be added), and then the tube is vacuum flame sealed. Next, the reaction system is heated to 140°C under anhydrous and oxygen-free conditions and the reaction is maintained for 24 hours. After the reaction is completed, it is quickly cooled to room temperature, and 2-3 times the amount of ice methanol as the reactant is added to precipitate the polymer. Subsequently, an aliphatic polycarbonate polymer is obtained by centrifugation to ensure the purity and quality of the polymer. Finally, the separated polymer is dried in a vacuum drying oven for 24 hours.
[0088] 2. Preparation of Conductive Ink
[0089] (1) Ink preparation: A synthetic aliphatic polycarbonate polymer (10 g), choline chloride (1 g), acrylic acid (1 g), zinc chloride (0.5 g) and a photocrosslinking agent benzophenone (0.2 g) were weighed in proportion; the above materials were added into a mixing container and stirred at a low speed in a stirrer for 10 minutes; then, the mixture was ultrasonically treated using an ultrasonic processor for 5 minutes.
[0090] Embodiment 2:
[0091] A preparation method of a photo-crosslinked conductive ink based on aliphatic polycarbonate comprises the following steps:
[0092] Step 1 is the same as the synthesis of step 1 in Example 1.
[0093] Step 2 Preparation of conductive ink: (1) Weigh the synthesized aliphatic polycarbonate polymer (8 g), choline chloride (1.2 g), acrylic acid (1.2 g), zinc chloride (0.4 g) and photocrosslinking agent benzophenone (0.2 g) in proportion. The other specific processes are the same as the corresponding steps in Example 1.
[0094] Embodiment 3:
[0095] Step 1 is the same as the synthesis of step 1 in Example 1.
[0096] Step 2 Preparation of conductive ink: (1) Weigh the synthesized aliphatic polycarbonate polymer (5 g), choline chloride (1 g), acrylic acid (1 g), zinc chloride (0.2 g) and photocrosslinking agent benzophenone (0.1 g) in proportion. The other specific processes are the same as the corresponding steps in Example 1.
[0097] Test analysis:
[0098] (1) Analysis of polymer properties: Analysis of polymer properties is an important step in evaluating the success of polymer synthesis. NMR and FTIR are used to analyze the structure of the polymer to confirm the success of polymer synthesis. NMR can provide information on the molecular structure of the polymer, including the length and branching of the chain, while FTIR is used to detect the functional groups in the polymer to confirm its chemical structure and composition. In addition, the molecular weight of the polymer is tested to ensure that it is within the expected range. The molecular weight is usually determined by methods such as GPC to evaluate the molecular weight distribution and uniformity of the polymer. The molecular weight of the polymer has an important influence on its physical and chemical properties, so the reaction conditions must be strictly controlled during the synthesis process to obtain the desired molecular weight. The thermal performance analysis of the polymer is equally important and is evaluated by thermogravimetric analysis (TGA) and differential scanning calorimetry (DSC). TGA is used to determine the thermal decomposition temperature of the polymer to ensure its stability in high temperature environments. DSC is used to determine the glass transition temperature (Tg) and melting temperature (Tm) of the polymer to understand its thermal properties. The thermal properties of the polymer directly affect its performance in practical applications, so comprehensive thermal performance testing is required.
[0099] (2) Conductive ink performance test: The printed samples are subjected to mechanical performance tests such as stretching, compression and bending to evaluate their strength, toughness and elastic modulus. Mechanical performance tests are usually performed using a universal material testing machine, and the test results can provide important basis for the practical application of the printed parts. In addition, according to relevant standards, the samples are subjected to biocompatibility tests to evaluate their safety in biomedical applications. Biocompatibility tests include cytotoxicity tests and biodegradability tests to ensure the safety and effectiveness of the samples in biological environments. Long-term stability tests are performed to evaluate the performance changes of the samples under different environmental conditions to ensure their reliability in practical applications. Long-term stability tests usually include performance evaluation under environmental conditions such as high temperature, high humidity and light to understand the durability and stability of the samples. During the performance test, the test results need to be statistically analyzed to evaluate whether the performance of the samples meets the expected standards. By analyzing the test data, the optimal application areas and usage conditions of the samples are determined. In addition, the long-term performance of the samples needs to be evaluated to ensure their reliability and safety in practical applications.
[0100] It should be noted that the present application is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present application are all included in the technical scope of the present application. In addition, without departing from the scope of the main purpose of the present application, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present application.
Claims
1. A photo-crosslinked conductive ink based on aliphatic polycarbonate, characterized in that: The invention comprises an aliphatic polycarbonate polymer, a plasticizer, a crosslinking agent, a crosslinking catalyst and a photocrosslinking agent.
2. The photo-crosslinked conductive ink based on aliphatic polycarbonate according to claim 1, characterized in that: The invention is composed of the following parts by weight: 5-15 parts by weight of aliphatic polycarbonate polymer, 0.5-1.5 parts by weight of plasticizer, 0.5-1.5 parts by weight of crosslinking agent, 0.2-0.8 parts by weight of crosslinking catalyst and 0.1-0.3 parts by weight of photocrosslinking agent.
3. The photo-crosslinked conductive ink based on aliphatic polycarbonate according to claim 1 or 2, characterized in that: The plasticizer is choline chloride, the cross-linking agent is acrylic acid, the cross-linking catalyst is zinc chloride, and the photo-cross-linking agent is benzophenone.
4. The photo-crosslinked conductive ink based on aliphatic polycarbonate according to claim 1 or 2, characterized in that: The viscosity of the ink is 200-300 mPa·s.
5. A method for preparing a photo-crosslinked conductive ink, comprising the following steps: (1) Synthetic aliphatic polycarbonate polymers; (2) Preparing conductive ink: adding aliphatic polycarbonate polymer, plasticizer, crosslinker, crosslinking catalyst and photocrosslinker in a certain proportion into a mixing container with a stirrer, stirring at a low speed for 5-15 minutes to ensure that the components are fully mixed; then, ultrasonically treating the mixture for 5-10 minutes using an ultrasonic processor.
6. The method for preparing the photo-crosslinked conductive ink according to claim 5, characterized in that: The synthesis of the aliphatic polycarbonate polymer comprises the following steps: first, polyethylene glycol and 5-methyl-5-carboxytrimethylene carbonate are added into a polymerization tube in a certain proportion under nitrogen protection, and a proper amount of polymerization catalyst is added and the tube is sealed with a vacuum flame; then, the reaction system is heated to 120-180° C. under anhydrous and oxygen-free conditions, and the reaction is maintained for 12-48 hours. After the reaction is completed, the reaction system is rapidly cooled to room temperature; then, the aliphatic polycarbonate polymer is obtained by centrifugal separation; and finally, the separated polymer is dried in a vacuum drying oven for 24 hours.
7. The method for preparing the photo-crosslinked conductive ink according to claim 6, characterized in that: After cooling to room temperature, icy methanol is added to precipitate the polymer; the amount of icy methanol added is 2-3 times the amount of the reactants; the amount of the polymer catalyst added is 0.3-0.6% of the total mass of the reactants.
8. The method for preparing the photo-crosslinked conductive ink according to claim 6, characterized in that: The mass ratio of the polyethylene glycol to MCC is 0.1-1.5, and the mass ratio of the polymerization catalyst to MCC is 0.01-0.03; the reaction temperature is 130-160° C., and the reaction time is 15-36 hours.
9. The method for preparing the photo-crosslinked conductive ink according to claim 5, characterized in that: The aliphatic polycarbonate polymer is 5-15 parts by weight, the plasticizer is 0.5-1.5 parts by weight of choline chloride, the crosslinking agent is 0.5-1.5 parts by weight of acrylic acid, the crosslinking catalyst is 0.2-0.8 parts by weight of zinc chloride, and the photocrosslinking agent is 0.1-0.3 parts by weight of benzophenone.
10. Use of the photo-crosslinked conductive ink according to any one of claims 1 to 5 or the conductive ink obtained by the preparation method according to any one of claims 6 to 9 in 3D printing.
Citation Information
Cited By
MXene doping-based polycarbonate conductive elastomer as well as preparation method and application thereof
CN120988448A
Polycarbonate-based conductive elastomer based on mxene doping and preparation method and application thereof
CN120988448B